ISLAMIC BANK PROFITABILITY: A STUDY OF ISLAMIC BANK IN INDONESIA - Dodi, Dodi; Supiyadi, Dedi; Arief, Meta; Nugraha, Nugraha (The International Journal of Business Review (The Jobs Review), 2018)
The aims of this paper are to examine the effect of factors that contribute towards the profitability of Islamic bank in Indonesia over the period 2008 – 2017. The research method used in this study is the explanatory method. We use secondary data obtained from the OJK to examine the effect of Bank Specific Macroeconomic Determinants of Islamic Bank Profitability and then analyse the data using GMM techniques. The result of the study found that only Bank Size of Bank Specific determinant had a positive effect both ROA and ROE while Capital, credit risk and Liquidity had a negative effect on the profitability of Islamic banking in Indonesia. Finally, the macroeconomic determinant found only inflation had positive effect while GDP had no significant effect on Islamic bank profitability. The result indicates that Islamic bank in Indonesia need well developed and well supported by government through independent regulation out of the bank of Indonesia, this mean Islamic bank could develop regulation and well Islamic product as conducted by Islamiclaw and Sunnah